Checklist to operationalize measurement characteristics of patient-reported outcome measures. Issue 1 (December 2016) - Francis, David; McPheeters, Melissa; Noud, Meaghan; Penson, David; Feurer, Irene
Abstract Background The purpose of this study was to advance a checklist of evaluative criteria designed to assess patient-reported outcome (PRO) measures' developmental measurement properties and applicability, which can be used by systematic reviewers, researchers, and clinicians with a varied range of expertise in psychometric measure development methodology. Methods A directed literature search was performed to identify original studies, textbooks, consensus guidelines, and published reports that propose criteria for assessing the quality of PRO measures. Recommendations from these sources were iteratively distilled into a checklist of key attributes. Preliminary items underwent evaluation through 24 cognitive interviews with clinicians and quantitative researchers. Six measurement theory methodological novices independently applied the final checklist to assess six PRO measures encompassing a variety of methods, applications, and clinical constructs. Agreement between novice and expert scores was assessed. Results The distillation process yielded an 18-item checklist with six domains: (1) conceptual model, (2) content validity, (3) reliability, (4) construct validity, (5) scoring and interpretation, and (6) respondent burden and presentation. With minimal instruction, good agreement in checklist item ratings was achieved between quantitative researchers with expertise in measurement theory and less experienced clinicians (mean kappa 0.70; range 0.66–0.87). Conclusions We present a simplified checklist that can help guide systematic reviewers, researchers, and clinicians with varied measurement theory expertise to evaluate the strengths and weakness of candidate PRO measures' developmental properties and the appropriateness for specific applications.